Neural respiratory drive predicts clinical deterioration and safe discharge in exacerbations of COPD. Issue 12 (20th July 2015) - Suh, Eui-Sik; Mandal, Swapna; Harding, Rachel; Ramsay, Michelle; Kamalanathan, Meera; Henderson, Katherine; O'Kane, Kevin; Douiri, Abdel; Hopkinson, Nicholas S; Polkey, Michael I; Rafferty, Gerrard; Murphy, Patrick B; et al.
Abstract : Rationale: Hospitalised patients with acute exacerbation of COPD may deteriorate despite treatment, with early readmission being common. Objectives: To investigate whether neural respiratory drive, measured using second intercostal space parasternal muscle electromyography (EMGpara ), would identify worsening dyspnoea and physician-defined inpatient clinical deterioration, and predict early readmission. Methods: Patients admitted to a single-site university hospital with exacerbation of COPD were enrolled. Spirometry, inspiratory capacity (IC), EMGpara, routine physiological parameters, modified early warning score (MEWS), modified Borg scale for dyspnoea and physician-defined episodes of deterioration were recorded daily until discharge. Readmissions at 14 and 28 days post discharge were recorded. Measurements and main results: 120 patients were recruited (age 70±9 years, forced expiratory volume in 1 s (FEV1 ) of 30.5±11.2%). Worsening dyspnoea, defined as at least one-point increase in Borg scale, was associated with increases in EMGpara%max and MEWS, whereas an increase in EMGpara%max alone was associated with physician-defined inpatient clinical deterioration. Admission-to-discharge change (Δ) in the normalised value of EMGpara (ΔEMGpara%max ) was inversely correlated with ΔFEV1 (r=−0.38, p<0.001) and ΔIC (r=−0.44, p<0.001). ΔEMGpara%max predicted 14-day readmission (OR 1.13, 95% 1.03 to 1.23) in the whole cohort and 28-day readmission in patients under 85 years (OR 1.09, 95% CI 1.01 to 1.18). Age (OR 1.08, 95% CI 1.03 to 1.14) and 12-month admission frequency (OR 1.29, 1.01 to 1.66), also predicted 28-day readmission in the whole cohort. Conclusions: Measurement of neural respiratory drive by EMGpara represents a novel physiological biomarker that may be helpful in detecting inpatient clinical deterioration and identifying the risk of early readmission among patients with exacerbations of COPD. Trial registration: NCT01361451.